Effect of shape formation on the accuracy of grinding ends while compensating for machine tool errors - Rudyk, Andrey; Chupryna, Volodymyr; Rudyk, Vladislav (Eastern-European Journal of Enterprise Technologies, 2021)
There are several general methods for correcting errors related to positioning the machine tool structural units. The task to achieve optimal manufacturing accuracy can be resolved by using a compatible solution to vector equations, a variation of the shape formation function, or applying a matrix of transfer coefficients. However, there is no mutual relationship between various calculation methods for the case of grinding flat surfaces. The methods should be simplified and tested for the elongated shape formation function while considering the links’ dimensions. This paper reports a study into the accuracy of grinding flat surfaces, determining and reducing the share of manufacturing errors. The content of variation matrices and transfer coefficients has been substantiated. The comparison of the orientation angles of the grinding machine headstock relative to the machine tool bed has demonstrated close results from all methods. These angles were taken as machine tool errors. The calculation error does not exceed 1.5 %. The experiments are consistent with the calculations. Different signs of the transfer coefficients in the orientation angles of grinding machine headstocks in the matrix make it possible to mutually compensate for the overall impact. The calculations have shown that the accuracy of the side-end machining is largely affected by a change in the orientation angle in the vertical plane. The effect exerted on the accuracy of individual mated parts by the machine tool structural units has been estimated. The calculations show that the error of positioning a part in the drum window acquires the highest absolute values and is random in nature, which requires a more accurate base positioning. The findings from both theoretical and experimental studies have been applied. The mathematical model makes it possible to determine the degree of scattering the end surface around the base plane via its variance. The measured trajectory provides diagnostic information about the sources of error in the machine tool assembly. A task to calculate the accuracy of the end-grinding machine tool can be solved for other models of machine tools in the same way